Novel variant NDM-11 and other NDM-1 variants in multidrug-resistant Escherichia coli from South India. (September 2018) - Rahman, Mohibur; Mukhopadhyay, Chiranjay; Rai, Ravi Prakash; Singh, Sanjay; Gupta, Shefali; Singh, Avinash; Pathak, Ashutosh; Prasad, Kashi Nath
Highlights: First report of a novel NDM-1 variant (NDM-11) from Escherichia coli in South India, from a snake bike wound infection. Other NDM variants were also found (one each of NDM-4 and NDM-8, and two NDM-5) recovered from clinical E. coli isolates. Other resistance genes ( bla TEM-1, bla CTX-M-15, bla VIM, bla CMY-2, rmtB and rmtC ) were associated with the NDM variants. Conjugation experiments revealed that the bla NDM variants were located on a transferable IncF plasmid of >100 kb. Expression of bla NDM-1 and bla NDM-11 in E. coli TOP10 showed no significant differences in MICs to β-lactams. Abstract: Objectives: Carbapenem resistance mediated by New Delhi metallo-β-lactamase 1 (NDM-1) and its variants has caused a major public-health concern worldwide. Here we report for the first time an Escherichia coli isolate positive for a novel variant (NDM-11). Methods: bla NDM genes were investigated in E. coli by PCR and sequencing, and bla NDM variants were further characterised. The susceptibility pattern of novel bla NDM-11 towards different antimicrobials was compared with bla NDM-1 by cloning and expression in E. coli TOP10. Results: A total of 33 carbapenem-resistant E. coli isolates were screened by PCR for the presence of bla NDM, of which 15 (45.5%) were positive. Sequencing of the PCR products revealed 10 isolates with NDM-1 and 5 isolates with NDM variants (one each of NDM-4, NDM-8 and NDM-11 and two NDM-5). Other resistance genes, including bla TEM-1, bla CTX-M-15, bla VIM, plasmid-encoded AmpC bla CMY-2 and 16S methyltransferases ( rmtB and rmtC ), were also associated with NDM variants in different combinations. The bla NDM variants were located on a transferable IncF-type plasmid of >100 kb. Pulsed-field gel electrophoresis (PFGE) showed that all five E. coli isolates were unrelated, and multilocus sequence typing (MLST) revealed that they all belonged to ST131. Expression of the bla NDM-1 and bla NDM-11 genes in E. coli TOP10 showed no significant difference in MICs to various β-lactams, including carbapenems. Conclusions: This study underlines the spread of NDM variants with other antimicrobial resistance genes in E. coli in South India. It also describes a novel NDM variant ( bla NDM-11 ) having an antimicrobial resistance pattern similar to bla NDM-1 .